In-Vitro antioxidant activities of ethanolic extract of whole plant of Ziziphus xylopyrus (Retz.) - M. Prabhu; G.Alagumanivasagam (International Journal of Pharmacy and Analytical Research, 2022)
In vitro antioxidant activities of ethanol extract of whole plant of Ziziphus xylopyrus(Retz.) was investigated. The free radical scavenging activity to evaluate by DPPH (2, 2-diphenyl -1- picrylhydrazyl) method, superoxide anion scavenging and iron chelating activity. DPPH radical scavenging activity of ethanolic extract and reference standard Rutin IC50 values was found to be 820 mg/ml and 460 mg/ml, nitric oxide scavenging activity of ethanolic extract and reference standard ascorbic acid IC50 values was found to be 510mg/ml and 420mg/ml and iron chelating activity of ethanolic extract and reference standard EDTA IC 50 values was found to be 320 mg/ml and 63mg/ml respectively. The above result of posse ss good an antioxidant activity when compare to the above all standard.